Space–time clustering patterns in childhood leukaemia support a role for infection - Birch, J M (Nature Publishing Group, 2000)
Previous studies of space–time clustering in childhood leukaemia have produced equivocal and inconsistent results. To address this issue we have used Manchester Children's Tumour Registry leukaemia data in space–time clustering analyses. Knox tests for space–time interactions between cases were applied with fixed thresholds of close in space, < 5 km and close in time < 1 year apart. Addresses at birth as well as diagnosis were utilized. Tests were repeated replacing geographical distance with distance to the Nth nearest neighbour. N was chosen such that the mean distance was 5 km. Data were also examined by a second order procedure based on K-functions. All methods showed highly significant evidence of space–time clustering based on place of birth and time of diagnosis, particularly for all leukaemias aged 0–14 and 0–4 years, and acute lymphoblastic leukaemia (ALL) 0–4 years. Some results based on location at diagnosis were significant but mainly gave larger P -values. The results are consistent with an infectious hypothesis. Furthermore, we found an excess of male cases over females involved in space–time pairs. We suggest this may be related to genetic differences in susceptibility to infection between males and females. These findings provide the basis for future studies to identify possible infectious agents. © 2000 Cancer Research Campaign